Perceptions of and intentions to adopt HIV pre-exposure prophylaxis among black men who have sex with men in Los Angeles. (December 2015) - Brooks, Ronald A; Landovitz, Raphael J; Regan, Rotrease; Lee, Sung-Jae; Allen, Vincent C
This study assessed perceptions of pre-exposure prophylaxis (PrEP) and their association with PrEP adoption intention among a convenience sample of 224 low socioeconomic status black men who have sex with men (BMSM) residing in Los Angeles. Participants received educational information about PrEP and completed an in-person interview. More than half (60%) of the participants indicated a high intention to adopt PrEP. Younger BMSM (18–29 years) were twice as likely to report a high intention to adopt PrEP compared to older BMSM (30+ years). Only 33% of participants were aware of PrEP and no participant had ever used PrEP. Negative perceptions were associated with a lower PrEP adoption intention and included being uncomfortable taking an HIV medicine when HIV-negative and not knowing if there are long-term side effects of taking an HIV medication. These findings suggest that BMSM may adopt PrEP but that negative perceptions may limit its uptake among this population. In order to facilitate PrEP adoption among BMSM targeted educational and community awareness programmes are needed to provide accurate information on the benefits of PrEP and to address the negative perceptions of PrEP held by local BMSM populations.